THE EFFECTIVITY OF CREDIT FOR BUSINESSES PROGRAM (KUR) DISTRIBUTION IN MALUKU AND MALUKU UTARA PROVINCES IN PERIOD OF 2010-2014 - Munandar, Yusuf . (JMBI UNSRAT (Jurnal Ilmiah Manajemen Bisnis dan Inovasi Universitas Sam Ratulangi)., 2017)
This research is conducted to know and explain the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Province and Maluku Utara Province. The research show that the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Province was decreasing that is the mistargeted ratio in 2014 as 1,57% was higher than the mistargeted ratio in 2010 as 0,00% and the trend of effectivity of CfB distribution in period of 2010-2014 in Maluku Utara Province was increasing that is the mistargeted ratio in 2014 as 1,85% was much lower than the mistargeted ratio in 2010 as 23,54%.Keywords : Credit for business, economic development, productive sector, poverty, working capital.